MODEL PEMBELAJARAN TAHFIDZUL QUR’AN KLASIKAL KELAS DI MA AL ITTIFAQIAH PONDOK PESANTREN AL ITTIFAQIAH INDRALAYA OGAN ILIR SUMATERA SELATAN - Umi Rosidah; Faridi (STIT Muhammadiyah Paciran Lamongan, 2024)
Tahfidzul Qur'an learning at the Al Ittifaqiah Islamic Boarding School, Indrlaaya Ogan Ilir, South Sumatra has become a superior school program whose tahfidz curriculum is included in the morning formal madrasa at the Madrasah Ibtidaiah, Madrasah Tsanawiyah and Madrasah Aliah levels, so that the curriculum is integrated into the madrasa curriculum, learning model Tahfidz at Madrasah Aliah All Ittifaqiah varies, there are those with individual memorization and classical classes, at Madrasah these classes are grouped into excellent class groups, both religious programs, Mathematics and Natural Sciences or Social Sciences. The target for memorizing the Qur'an is adjusted to the excellent class program. Regular classes (non excellent classes) still have a target for memorizing the Qur'an, namely 4 juz in 3 years. The aim of this research is to determine the learning model in class XII Excellent MIPA madrasah aliah al Ittifaqiah Indralaya Ogan Ilir South Sumatra. The type of research used uses case studies. The approach used is a qualitative descriptive approach. The primary data sources for this research are the Al Ittifaqiah Islamic Boarding School Quality Assurance Center Program Coordinator, the head of the madrasah, the deputy head of the madrasah in charge of the excellent class, the class XII students of the Al Ittifaqiah MIPA program. Secondary data is a book of students' memorization achievements, reports on the progress of students' memorization and photos of students' activities in tahfidzul Qur'an. The data collection methods for this research are observation, interviews and documentation. The results of the research on the tahfidz learning model at Madrasah Aliah al Ittifaqiah are classical classes by memorizing them together and repeating perwaqof at least seven times in memorizing the Qur'an on a new memorized page, memorizing the Qur'an followed by individual memorization deposits to the supervisor teacher memorize the Qur'an as a daily evaluation, then the results of memorizing the Qur'an will be of better quality and will be very enthusiastic about memorizing, it will be fun and it will feel easy to memorize the Qur'an because it is memorized in a classical class. As for the evaluation of tahfidzul Qur'an learning, daily evaluations of new memorization are carried out, deposits of 10 pages (half juz) of takrir every day, evaluation at the end of each juz (Data on the number of memorized reading errors by calculating the number of memorized errors) weekly evaluation, monthly evaluation, end of semester evaluation , end of year evaluation, evaluation before graduation by rote, evaluation on mujahadah ula, mujahadah tsaniah and mujahadah kubro (mujahadah tsalitsah).